CRITICAL DISCOURSE ANALYSIS OF REPRESENTATION OF WOMAN EMPOWERMENT IN THE “NEW WOMAN” SONG’S LYRICS BY LALISA FEAT ROSALIA - THE ENGLISH VERSION - Afiyanti, Sylvi Nur; Heribertus Binawan (Bajang Institute, 2025)
This research uses Norman Fairclough's Critical Discourse Analysis (CDA) paradigm to analyze how Lisa and Rosalía's song